Scholarships, fellowships, and loans a guide to education-related financial aid programs for students and professionals. (Gale virtual reference library, 2009)
Provides sources of scholarships, fellowships, loans, internships, work study, and other education-related financial aid at all levels of study. Includes a summary of programs sponsored by the federal government. Also includes a state-by-state listing of agencies that users can contact in their home state.